Performance Analysis of Optimum Combiner in Power Limited Cognitive Radios with Multiple Primary Interferers - Bindra, Kavita Vij; Khanna, Rajesh; Sharma, Surbhi (Elektronika ir Elektrotechnika, 2018)
This paper investigates the performance of power limited Cognitive Radio system with optimum combining  at the cognitive user receiver  under the influence of interference from multiple primary users’ transmitters (Lt) in flat Rayleigh fading channels. An approximate analytical result of the probability density function of maximum signal-to-interference ratio at the output of CR-OC receiver is derived. Using this derived PDF, the closed form expressions for the performance metrics viz. Average post processed SIR, Ergodic capacity, Average bit error rate and outage probability of CR-OC system are derived by taking into account peak interference power constraint denoted by ‘Q’ at PU-Rx. Based on the achieved result, it is concluded that the performance of the proposed system degrades when number of primary interferers exceeds from  Lt=3. Analytical results for CR-OC system are validated through Monte Carlo simulations also.DOI: http://dx.doi.org/10.5755/j01.eie.24.1.20159